(untitled) (Carte Romanze, 2019)
The Riccardiana Library in Florence houses a “curious” manuscript of Perceval by Chrétien de Troyes, known for the works of Keith Busby about the manuscript tradition of Chrétien’s romans, but ignored by the editors because of its lack of authority. The essay tries to deepen its material aspects, to analyse the peculiarities of the main copyist, and to verify two “suggestive” hypotheses by Busby himself: the manuscript could have been written under dictation, and revised by four correctors through one or more manuscripts, and not on the basis of its model (so by contamination).